Nowe kino rosyjskie wobec tradycji literackiej i filmowej - Waligórska-Olejniczak, Beata; Przybysz, Anna; Królikiewicz, Natalia; Kaźmierczak, Natalia; Bogusz-Tessmar, Paulina (Uniwersytet im. Adama Mickiewicza w Poznaniu, Instytut Filologii Rosyjskiej i Ukraińskiej, 2017)
The monograph entitled New Russian Cinema in View of Literary and Film Tradition consists of 6 basic parts: introduction and 5 chapters, which are devoted to the interpretation of five different films made by acclaimed contemporary directors. Chapter 1 is the attempt of reading the original film Doctor Ragin (2004), made by Kirill Serebrennikov on the basis of Anton Chekhov’s story Chamber no. 6. The aforementioned artist is considered one of the most famous and talented Russian directors, who work both in the domain of theatre and cinematography. In Doctor Ragin he managed to show the illusory side of the difference between a hospital room and the world outside. The main problem of the analyzed work is the history of madness of the whole country, in which there are no clear borders between madhouses and the everyday life of the society which claims to be sane. Chamber no. 6 is shown in the film as the safety option, a kind of “island”, asylum, where a man can protect himself against total madness. The film can be read as the diagnosis of the world which is insane, showing the roots of mental problems, which can be found both in the past and in the present. Chapter 2 tries to answer the question to what extent the problems in Fyodor Dostoyevsky’s novel are still understandable and up-to-date for the contemporary reader. To do so we focus on Menahem Golan’s Crime and Punishment adaptation. Translating the dramatic structure of the novel to the language of film, the director is fixing his attention on the central thought in the novel – hope – which can be associated with the spiritual and moral rebirth of man in the context of cultural and social reevaluation. This realignment ousts the bond with the source of the life-giving power (God) and supersedes the love for the Other from the universal awareness. Through distinctly extended sign-symbolic layer of the film, which sends the spectator beyond visual contexts, the director is trying to fulfil basic aims of the film: giving information, teaching and edifying.

Chapter 3 focuses on the artistic function of the ordinary in the film The River by Aleksei Balabanov, an unfinished work based on W. Sieroszewski's story The bottom of misery. The exact reconstruction of everyday Yakut's life, their customs, language and folklore, allows us to put The River in the context of the tradition of ethnographic films. The large amount of everyday life details in the visual layer creates symbolic meaning of adapted ethnographic elements (such as grass cutting, repairing fishing nets, preparing meals, clothes, items etc.). Intended mythologization of the depicted world leads to the process of renewal and reinterpretation of archetypes. The film orientation towards archetypal symbols can be noticed in the tendency of the artist's creative adaptation of the cultural heritage of the Nation of the North and in the attempt of universalization of aesthetic values. Balabanov seems to place the new tragic model, constructed by the storyline, in the space of everydayness. The artistic device, aimed at the transformation of the classic perception of the tragic, is primarily based on excluding the tragic from the sphere of sublimity, destructing pathos as well as showing semantic depth of everyday life elements. Chapter 4 concentrates on the film The Return by Andrey Zvyagintsev in the light of the director’s artistic method. The aim of this part of the book is the attempt to find elements of Zvyagintsev’s artistic world, which can be defined as original and integral components of his artistic method. Therefore, as a result of the analysis of some selected scenes we come to the conclusion that Zvyagintsev's works can be marked by such characteristic features as symmetrically constructed frames, appearance of different variants of geometric figures in the space of the frame, dominance of long, static frames, presence of blurred and dark colors, meaningful silence, semispherical (in Yuri Lotman’s understanding) density of individual frames. In Zvyagintsev’s film we can also observe frequent repetition of the motifs of water, photograph, sacrifice, as well as biblical and cultural-mythological symbols. The repetition of various motifs is used by Zvyagintsev as the artistic device of the loop, the sign of cyclicality and compositional framework. We can also notice that the titles of the films are very important, they can be treated as a kind of hint, an interpretation key, using which the viewer is able to perceive the picture on a deeper level. Chapter 5 aims to interpret metaphors of death in Renata Litvinova’s film The Last Tale of Rita (Последняя сказка Риты, 2012) in the context of Susan Sontag’s concepts, which were expressed first of all in her work Illness as Metaphor. The analysis proves not only the relevance of the American writer’s thoughts in the domain of myths and images associated with death, which are present in collective memory, it also shows a number of similarities between the style of retro glamour adapted by the director and Sontag’s philosophy of new sensitivity called camp. As a result of the process of contextualization the attention is turned to the aesthetization procedures used by Litvinova in order to romanticize and neutralize the phenomenon of death. They are introduced due to the adaptation of carnival stylization as well as intertextual references to the poetics of surrealism and fairy tales. The analysis focuses on the process of understanding death metaphors in the text of the film, which at the same time constitutes the attempt of decoding symbolic leitmotivs, methods of theatralization and ritualization of behavior, including selected montage solutions used in the movie.
Keywords: Litwinowa; Zwiagincew; Балабанов; Golan; Серебренников; adaptacja; Dostojewski; Sieroszewski; Czechow